Chemosensitizing effect of apigenin on T-ALL cell therapy - Huseynova, Nigar; Baran, Züleyha; Khalilov, Rovshan; Mammadova, Afat; Baran, Yusuf (Frontiers in Pharmacology, 2025)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematological malignancy with limited therapeutic options and frequent treatment-associated toxicities. L-asparaginase, a cornerstone in T-ALL therapy, is often restricted by hypersensitivity reactions and systemic side effects, highlighting the need for safer strategies to enhance its efficacy. This study investigated the potential of apigenin, a naturally occurring flavonoid with antioxidant and pro-apoptotic properties, to act as a chemosensitizer for L-asparaginase in MOLT-4 T-ALL cells. Cytotoxicity was assessed using the MTT assay, apoptosis by Annexin V/PI staining, cell cycle distribution by flow cytometry, and mitochondrial membrane potential by JC-1 staining. Both apigenin and L-asparaginase produced dose- and time-dependent cytotoxicity, with combination treatment resulting in reduced IC50 values. Apoptotic analysis showed significantly higher apoptosis in the combination-treated groups than in single-agent groups. Cell cycle analysis revealed that apigenin induced S-phase arrest and L-asparaginase induced G1-phase arrest, while the combination disrupted cell cycle progression at multiple checkpoints. JC-1 assay further demonstrated enhanced mitochondrial depolarization, with up to a 29.2-fold increase in cytoplasmic-to-mitochondrial fluorescence ratio in combination therapy compared to L-asparaginase alone. These findings indicate that apigenin potentiates L-asparaginase-induced cytotoxicity through mitochondrial dysfunction and intrinsic apoptotic signaling. The combined use of apigenin and L-asparaginase may provide a novel strategy to improve therapeutic efficacy in T-ALL while potentially reducing the toxicity associated with high-dose L-asparaginase monotherapy.